Case Report: Severe IgE-mediated hypersensitivity to carboxymethylcellulose with tolerance to crosscarmellose and microcrystalline cellulose - Schreiber, Rhea; Guillet, Carole (Frontiers in Allergy, 2025)
We present a rare case of severe IgE-mediated hypersensitivity to carboxymethylcellulose (CMC) following an intraarticular knee injection with triamcinolone acetonide (Triamcort®). The patient experienced a grade IV anaphylactic reaction shortly after administration. Diagnostic workup, including skin prick testing and basophil activation test, confirmed sensitization to CMC. Importantly, the patient tolerated medications containing crosscarmellose and microcrystalline cellulose without adverse reactions, suggesting no clinically relevant cross-reactivity. This case highlights the need to consider excipients such as CMC as potential triggers of severe allergic reactions especially in cases of unexplained anaphylaxis to injectable medication and underscores the importance of thorough allergological assessment to ensure safe future treatments.